Climate Change and Social Movements Civil Society and the Development of National Climate Change Policy - Nulman, Eugene; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2015)
Climate Change and Social Movements is a riveting and thorough exploration of three important campaigns to influence climate change policy in the United Kingdom. The author delves deep into the campaigns and illuminates the way policymakers think about and respond to social movements.
Keywords: Environment; Climate change; Sustainable development; Environmental policy; Social policy; Environmental economics; Environment; Environmental Politics; Environmental Policy; Sustainable Development; Environmental Economics; Social Policy; Climate Change; Electronic books